Strategi Peningkatan Pengumpulan Zakat, Infak dan Sedekah Pada Lembaga Amil Zakat Al-Ihsan Jawa Tengah - Muhammad Tho'in; Reno Yakob Andrian (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine an effective strategy method used to increase ZIS fundraising in LAZiS Central Java and to find out how to evaluate strategies used to increase ZIS fundraising in LAZiS Central Java. An effective strategy in raising ZIS ia very much needed to be used in financing the program’s operational activities of the Intitution which ultimately achieve the vision and mission of the Institute. The analytical method used in this research is a qualitative approach. Data sources and data collection techniques in this study were interview with employees and staff of ZIS collection and sources of written data from documents, archives and other documents. The result showed that in raising ZIS funds, LAZiS Central Java used traditional methods and modern strategies. As for the two ZIS funraising strategies used by LAZiS Central Java, the most effective strategy in raising ZIS funds is the strategy that uses traditional methods. To determine the effectiveness of the strategy used, LAZiS Central Java routinely conduct evaluations of the strategies used. This evaluation is carried out every week and each month includes each section.